2009
DOI: 10.1021/jm900878u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 2-Heteroarylthioalkanoic Acid Analogues of Clofibric Acid as Peroxisome Proliferator-Activated Receptor α Agonists

Abstract: A series of 2-heteroarylthioalkanoic acids were synthesized through systematic structural modifications of clofibric acid and evaluated for human peroxisome proliferator-activated receptor alpha (PPARalpha) transactivation activity, with the aim of obtaining new hypolipidemic compounds. Some thiophene and benzothiazole derivatives showing a good activation of the receptor alpha were screened for activity against the PPARgamma isoform. The gene induction of selected compounds was also investigated in the human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…In 2009, several 2-benzothiazolylthioalkanoic acids 39 (Figure 18) were synthesized and evaluated for their human PPARγ transactivation activity [109]. Overall, the potencies of some newly designed agonists were slightly higher than those of typical fibrates, such as clofibrate.…”
Section: Biologically Active 2-mercaptobenzothiazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, several 2-benzothiazolylthioalkanoic acids 39 (Figure 18) were synthesized and evaluated for their human PPARγ transactivation activity [109]. Overall, the potencies of some newly designed agonists were slightly higher than those of typical fibrates, such as clofibrate.…”
Section: Biologically Active 2-mercaptobenzothiazolesmentioning
confidence: 99%
“…Another group of researchers synthesized a series of 2-benzothiazolylthioalkanoic acids 52 (Figure 29) through systematic structural modifications of clofibric acid and evaluated them for human PPARα transactivation activity, with the aim of obtaining new hypolipidemic compounds [125]. Overall, the potencies of some newly designed agonists were slightly higher than those of typical fibrates, such as clofibrate.…”
Section: Biologically Active 2-mercaptobenzothiazolesmentioning
confidence: 99%
“…These compounds, considered as clofibric acid analogues, were basically PPAR agonists with the S isomers more potent than the R counterparts. In the series of optically active ligands, the best findings were obtained with the isomer (108) [127]. …”
Section: -Substituted Aryloxyacetic Acid Derivatives (Fibrates)mentioning
confidence: 99%
“…In previous papers from the Italian co‐authors’ laboratories1,2 synthesis and in vitro bioactivity data have been reported for a representative series of structurally diverse derivatives of clofibric acid, in particular heteroarylalkanoic analogues (Scheme 1, Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Especially interesting from the point of view of a search for potential drugs, guided by quantitative structure‐activity relationships (QSAR), appeared to be the EC 50 values, determined for 18 agents in the human peroxisome proliferator‐activated receptor α (PPARα) transactivation test 2. These EC 50 data (in µM) spanned three orders of magnitude and were evenly distributed (Table 1S in Supporting Information).…”
Section: Introductionmentioning
confidence: 99%